Gender and Social Economic Factors Affecting IPM Knowledge Acquisition and Application: A Case Study of Coffee Farmer Group Members in Bugisu, Uganda - Ochago, R.; Mangheni , M. N; Miiro , R. F (Asian Journal of Agriculture and Rural Development, 2016)
The paper presents findings from a study conducted to determine men and women farmers’ knowledge of the coffee Stem Borer IPM practices and socio-economic factors influencing the level of farmers’ knowledge in Bugisu sub region, Uganda. A post training cross sectional survey of 71 men and 55 women members of coffee IPM groups who had participated in training on coffee stem borer IPM was conducted. The knowledge of training participants was computed using a knowledge index and difference between knowledge levels of men and women farmers compared using independent t test. It was found that men had a significantly higher mean score on the IPM knowledge index compared to women. In addition, there was a significant correlation between knowledge of CSB IPM with gender, educational level, marital status, household labor, coffee acreage, years in the coffee group and women’s mobility. The results imply that greater competence is achieved when group training methods were complemented with more personal extension methods such as on farm visits. In addition, targeting various social groups including women, youth, and those who are not members of social and economic groups with the intention of addressing their unique needs would boost their IPM knowledge level. For women, knowledge acquisition is enhanced when gender based barriers to their participation in learning groups are addressed.